Notes (1) on Two Tribula or Threshing-Sledges, having their under surfaces studded with rows of chipped flints, for threshing corn on a threshing-floor, from Cavalla in European Turkey, now presented to the Museum; and (2) on Primitive Implements and Weap - Mann, Ludovic McLellan (Proceedings of the Society of Antiquaries of Scotland, 1904)